Effective maternal, newborn and child health programming among Rohingya refugees in Cox’s Bazar, Bangladesh: Implementation challenges and potential solutions - Sarker, Malabika; Saha, Avijit; Matin, Mowtushi; Mehjabeen, Saima; Tamim, Malika Asia; Sharkey, Alyssa B.; Kim, Minjoon; Nyankesha, Ele´vanie U.; Widiati, Yulia; Shahabuddin, A. S. M. (PLOS ONE, 2022)
This article was published in The PLOS One [ © 2020 Sarker et al. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.1371/journal.pone.0230732 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0230732